Sexual education for university students and the community in a european project: study protocol - I. Soto-Fernández; R. Fernández-Cézar; A. M. Aguiar Frias; H. Dias; C. Santiago; C. Gradellini; V. Aaberg; V. García-López; S. Gómez-Cantarino (BMC Nursing, 2023)
Abstract Background The World Health Organisation (WHO) calls on stakeholders to give Higher Education a key educational importance for the future of Europe. Within the content of the training programmes at university, sexuality emerges as a relevant topic in the nursing degree, to promote integral health from a holistic perspective. However, research on the presence of sexuality at the curricular level in Higher Education suggests that it is incomplete and underdeveloped. Methods This is a protocol for a long-term, multi-centre, exploratory, descriptive, and cross-sectional study with a quantitative and qualitative approach lasting two years. The research will be carried out in the educational community, including, on the one hand, students, and professors and health professionals of nursing programmes from five universities in different parts of the world (Portugal, Spain, Italy, and the United States), and on the other hand, women, young people, and immigrants from these communities. The study will have several target populations. Firstly, the target is nursing students, with whom the aim is to define their perspective on the sexuality content taught at the university, and their level of knowledge. Secondly university professors and health professionals, with whom we will check their perspective on sexuality in the classroom, as well as their level of knowledge in this field. And finally, we will work with the community (women, young people, and immigrants) to whom we will try to bring sexuality from a useful and enjoyable perspective. In order to measure these variables in the protocol, instruments such as questionnaires and semi-structured interviews will be used. During data collection, ethical principles will be guaranteed and informed consent will be requested from the participants. Discussion The results of the research will have a high curricular impact on the educational community, and will last over time, since the tools generated in the project will be included as part of nursing training programmes. In addition, participation in the project will improve health education for health professionals and at the community level on sexuality in both urban and rural populations.